Pomiferin Exerts Antineuroinflammatory Effects through Activating Akt/Nrf2 Pathway and Inhibiting NF-κB Pathway - Yan Zhao; Yuxuan Sang; Yanan Sun; Jie Wu (Mediators of Inflammation)
Background. Neurodegenerative diseases, including Alzheimer’s disease, Parkinson’s disease, and Huntington’s disease, are mainly characterized by progressive motor, sensory, or cognitive dysfunction in patients. Such diseases mostly occur in middle-aged and elderly people, and there is no effective cure. Studies have shown that neurodegenerative diseases are accompanied by neuroinflammation. The proinflammatory mediators produced neuroinflammation further damage neurons and aggravate the process of neurodegenerative diseases. Therefore, inhibiting neuroinflammation might be an effective way to alleviate neurodegenerative diseases. Pomiferin extracted from the fruit of the orange mulberry has a wide range of antioxidation and anti-inflammatory effects in peripheral tissues. However, it is not clear whether it plays a role on neuroinflammation. Methods. In our experiment, we studied the effect of Pomiferin on BV2 cell inflammation and its mechanism with cck-8, LDH, quantitative PCR, and ELISA and methods. We then investigated the effect of Pomiferin on the classical inflammatory pathway by Western blot methods. Results. The results showed that Pomiferin inhibited the production of ROS, NO, and proinflammatory mediators (IL-6, TNF-α, iNOS, and COX2) in BV2 cells. Further mechanism studies showed that Pomiferin activated the Akt/Nrf2 pathway and inhibited the NF-κB pathway. Conclusion. Our study demonstrated that Pomiferin exerts antineuroinflammatory effects through activating Akt/Nrf2 pathway and inhibiting NF-κB pathway.